Modern Modern Community Capital Social (Case Study on Increasing the Popularity of Millennial Youtubers in Makassar City) - Andry Wijaya; Suparman Abdullah (LEGAL BRIEF, 2022)
YouTube has become an internet media that is in demand by various audiences around the world. Youtuber is a new job that is synonymous with Millennials in this 4.0 industrial era. This study aims to determine the use of social capital trust by youtubers in increasing popularity, as well as to determine the use of social capital linking youtubers in increasing popularity. This study uses a qualitative approach, with informants namely millennial youtubers who live in the city of Makassar. Data collection techniques through observation, interviews and documentation, with data analysis techniques using: data reduction, data presentation and drawing conclusions and verification. The results of the study show that trust social capital is widely used by youtubers to increase their popularity, in this case increasing the number of subscribers and viewers on their youtube channel. Many YouTubers use social capital linking or networks to increase the number of subscribers and viewers. The social capital of the network used is by utilizing the friendship and community of YouTubers in the process of designing content, taking videos, editing to uploading videos and socializing YouTube channels in order to minimize the cost of managing YouTube channels for YouTubers.